"Criminal" Law Politics Regarding the Legalization of Citizenship Documents (Apostille) in Indonesia - Adi Mansar; Ferry Susanto Limbong (Randwick International of Social Science Journal, 2023)
The legalization of citizenship documents is not only an administrative matter in countries whose administrative systems exist throughout the world. Philosophically, the purpose of legalization is to protect and create legal certainty for every user. Therefore it is necessary to analyze the political role of criminal law about the apostille and which citizenship documents are part of the apostille. Because Indonesia's international interaction policy resulted in the ratification of many national conventions, including the Congress on the Elimination of Legalization of Foreign Public Documents. The use of all documents is the right and obligation of each person to comply with all applicable regulations in different countries. The use of documents and their evidentiary system regulated in the Decree of the Minister of Law and Human Rights Number 6 of 2022 is a national policy that provides legal protection and certainty to all users and those who have the authority to legalize citizen documents. The practices offered are administrative and public (criminal) rights. The emergence of a criminal justice policy regarding the authentication of citizenship documents that applies in 121 countries is urgently needed to protect, for example, parties or bodies authorized to carry out authentication. One of the state institutions authorized to legalize civil documents is a notary. Based on the Notary Law, the position of Notary is called an official who has the authority to handle special requests from the public related to Notaries. It should be noted that documents that can be used both domestically and abroad must be legalized by 5 (five) authorities, namely the Document Authority, the Indonesian Ministry of Law and Human Rights, the Ministry of Foreign Affairs and the Consulate. Ministry of Foreign Affairs of the destination country and Ministry of Foreign Affairs of the destination country.